(untitled) (The Pakistan Development Review, 2017)
Previous studies in Pakistan have established the number of pupil, parents, household, and community characteristics as determinants of primary school enrolment. However, treatment of the role of the household power structure in these studies is limited to the inclusion of a single dummy variable for female headship. Present study estimates separate probit regressions for different types of headships, hence allowing for an analysis of the power structure of the household and its impact on other explanatory variables. In addition to confirming the findings of previous studies, this study concludes that mother‘s headship results in greater positive influence of her own education and the economic status of the household on child‘s primary school enrolment. Father‘s headship in this regard has only limited influence. JEL Classification: C25, J16, I21 Keywords: Probit Models, School Enrolment, Gender Issues